Pan Trinbago Luring Bands With Promises' - Unknown (Daily Express)
The Southern Steelband Movement (SSM) has accused Pan Trinbago of offering cash incentives to steelbands although the incentives have not yet been approved by government. Winston Gibson, secretary of SSM stated that Pan Trinbago was offering a $5,000 appearance fee to steelbands in the Panorama competition which would draw many steelbands away from the SSM Panorama competition.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago -- Finance; Pan Trinbago (Organization); Steel bands (Music) -- Administration -- Trinidad and Tobago